(untitled) (Marketing Journal, 2026)
This article analyzes the current state of fruit and vegetable exports in Bukhara region, existing problems and marketing approaches. During the research, the agricultural potential of the region, export indicators, logistics infrastructure and marketing s trategies were studied. The research results show that the export potential of the region is not fully utilized, cold chain infrastructure is insufficient and marketing activities are not systematically organized.